A Novel Band-Stop Filter with Band-Pass, High-Pass, and Low-Pass Negative Group Delay Characteristics - Aixia Yuan; Shaojun Fang; Zhongbao Wang; Hongmei Liu; Hongjun Zhang (International Journal of Antennas and Propagation)
A band-stop filter with three different negative group delay functions in the passband, namely, band pass, high pass and low pass, is proposed, which has small insertion loss. The capacitance, inductance, and resistance meet different conditions, and the circuit can realize three different negative group delay characteristics. The theoretical calculation and equation derivation are given. A band-stop filter with negative group delay function is fabricated, and the measured results are basically consistent with the simulation results. The correctness of the design is verified.